Considering an Islamic Framework in the Study of Philosophy of History - Muhammad Faqih Nidzom; Fiqhi Akbar Rafsanjani; Rochmad Rochmad (University of Darussalam Gontor, Indonesia, 2023)
This article proposes an Islamic framework for the study of philosophy of history, from its object of study, theoretical framework, and its case study of Ibn Khaldun’s thought. This research is based on literature and qualitative research, and it uses the descriptive-analytical methods. This article concludes that philosophy of history is identical to the world of civilization (‘umrān al-‘ālam), and encompasses a whole human civilization. Civilization means an outcome of the dynamic concept, and the civilization mobilizes a pre-civilizational society to have a part in history and generate an appropriate system and ideas. The main method,then, is observing nature and society's laws that control historical events (thabāi' al-'umrān).The study of history, including civilization, can describe things behind an event, not restricted to when, what, and how an event happened, but also explain why it occurred. Therefore, it contains an observation, the effort to find the truth (tahqīq), and deep knowledge of history's substance, essence, and causality. This meaning is rooted in philosophy and deserves to be accounted for as a branch of philosophy.